The Quest for Independent Living: Youth Shelter as a Critical Moment in Young Adults’ Life Course - Miia, Lähde; Mölkänen, Jenni (2021)
In this chapter, we explore accounts and challenges of ‘independence’ of young adults, aged 18-24, who have sought support from the Youth Shelters (YS) run by the Finnish Red Cross. Many of these young adults have been customers of various welfare services, and their trajectories to adulthood diverge from the normative model of life course that expects smooth and timely transitions from education to work and from childhood nuclear family to independent living (see Shanahan 2000; Blatterer 2007; Aapola & Ketokivi 2005; Brunila et al 2019: 109). By drawing on data from qualitative interviews, we analyse young adults’ needs for help in transition to adulthood. We focus on the significance of the third sector service provider Youth Shelters Peer reviewed